2016
DOI: 10.1186/s40101-016-0119-1
|View full text |Cite
|
Sign up to set email alerts
|

Height correlates with dyslipidemia in non-overweight middle-aged Japanese men

Abstract: BackgroundOur previous study showed that height is inversely associated with the risk of stroke in middle-aged Japanese men, particularly in those with a low body mass index (BMI). Since height is regarded as a surrogate maker of childhood social and physical condition, while BMI may reflect primarily on the current physical condition, a detailed analysis of those with a lower BMI may elucidate the effects of childhood conditions. On the other hand, dyslipidemia is recognized as a prominent risk factor for car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Our additional analysis which was limited to participants with a BMI < 25 kg/m 2 showed slightly stronger associations with regard to short stature and reduced MTP in relation to SNP rs3782886. Since an analysis limited to participants with a lower BMI might elucidate the influence of childhood circumstances (including genetic factors) [ 9 , 12 ], the additional analysis also supports the present conclusion that a genetic factor may influence the association between height and reduced MTP.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our additional analysis which was limited to participants with a BMI < 25 kg/m 2 showed slightly stronger associations with regard to short stature and reduced MTP in relation to SNP rs3782886. Since an analysis limited to participants with a lower BMI might elucidate the influence of childhood circumstances (including genetic factors) [ 9 , 12 ], the additional analysis also supports the present conclusion that a genetic factor may influence the association between height and reduced MTP.…”
Section: Discussionsupporting
confidence: 80%
“…Since a previous study of community-dwelling elderly individuals reported that individuals in the lowest tertiles of tongue pressure had lower scores in the muscle function test (handgrip strength, jump height, and jump power) [ 8 ] than individuals in other tertiles, we defined reduced MTP as a tongue pressure in the lowest tertile of the study population (<26.5 kPa for men and <24.1 kPa for women). And short stature was defined as a height level at or under the 25th percentile of the study population (<158.0 cm for men and <145.0 cm for women) since these participants may have cardiovascular risk factors determined by childhood social and physical conditions (including genetic factors) [ 9 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential limitations of this study warrant consideration. Because creatinine clearance data were not available and estimated glomerular filtration rate (GFR) is not an effective tool for evaluating kidney function for determining the latter’s associations with various body heights [47, 33, 34], we were not able to perform an analysis adjusted for exact renal function. However, our study showed that the association between height and circulatory CD34-positive cell remained significant even after adjustment for serum creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships of cholesterol or CVD to height have not been explored in the major cohorts that study cardiovascular risk factors in children, such as Bogalusa Heart Study, Muscatine or in analyses of the National Health and Education Nutrition Examination Survey other than to note that a greater change in height predicts a larger LDL decrease over time (5)(6)(7). Shimizu et al showed lower LDL levels in taller adult Japanese males, unless the BMI was  25 kg/m 2 (8). The odds ratio of dyslipidemia (LDL > 140 mg/dl or triglycerides 150 mg/dl) fell from the first (shortest) to fourth (tallest) quartile in those under 25 kg/m 2 , but was nonsignificant for those 25 kg/m 2 .…”
mentioning
confidence: 99%